Aggressive chemotherapy aimed at obviating radiation in two very young infants with disseminated anaplastic ependymoma - Maria Carter-Febres; Emily A. Sloan; Melike Pekmezci; Angelica R. Putnam; Luke Linscott; Samuel Cheshier; Kenneth Aldape; Carol S. Bruggers (Elsevier, 2021)
Ependymomas account for nearly 10% of pediatric intracranial tumors. Surgical resection followed by focal radiation constitutes standard management for children older than 1 year when diagnosed. No standard therapy exists for the extremely vulnerable population of infants diagnosed under 12 months-old, including those with leptomeningeal disease dissemination, when nervous system development is extraordinarily rapid and complex. Chemotherapy offers a promising strategy to avoid well-documented radiation-induced toxicities, especially marked neurocognitive impairment. This report describes successful chemotherapy that obviated radiation in two infants with ependymoma associated with leptomeningeal dissemination, PF-A molecular subtype in one and C11orf95-RELA gene fusion in the other. It provides a proof of concept that individualized chemotherapy in select patients can minimize radiation-associated adverse neurocognitive disabilities while promoting cure, despite high-risk clinical and molecular features.